Effects of morphine on catecholamine release and arrhythmias evoked by myocardial ischaemia in rats. - Addicks, K. (1987)
The effects of morphine (10 mg kg-1 i.p.) on haemodynamics, arrhythmias and plasma and myocardial catecholamines (CA) were studied after coronary artery occlusion in anaesthetized rats. Myocardial intraneuronal CA were assessed histofluorimetrically and CA concentrations measured by high performance liquid chromatography. Morphine increased blood pressure, presumably due to higher plasma noradrenaline (NA) concentrations found in morphine-treated rats. Morphine increased the area of catecholamine-containing fluorescing neurones in the myocardium (as a percentage of total field area) 60 min after sham-operation (0.87 +/- 0.07%) or occlusion (0.57 +/- 0.05%) compared to untreated animals (0.67 +/- 0.06 and 0.38 +/- 0.03% respectively). Tissue NA content was not significantly affected by coronary occlusion and/or morphine within the first 60 min. Morphine had no effect on ischaemia-induced arrhythmias. Whether the higher intraneuronal NA content following morphine resulted from reduced central sympathetic outflow to the heart, presynaptic inhibition of NA release, or increased uptake due to higher plasma concentrations is unclear. Ischaemia-induced local NA release appears independent of these mechanisms, as it was unaffected by morphine.